Table of Content - - (Journal of Arabic Language Sciences and Literature, 2024)
Table of Content: 1. The popular proverb between depicting experience and the frameworks of criticism Dr. Omar Mahmoud Assi 2. Reference and its role in textual cohesion (The Two Holy Mosques’ sermons in the 2020 Corona crisis as an example) Ms. Amina Muhammad Al-Hamrani, Dr. Hoda Eid Bassiouni 3. The semantic and lexical level of bilingualism in protest ages Co-Prof. Mohammad Khaled Al-Rhawi 4. What al-Qatrab uniquely mentioned about Yunus bin Habib in the topics of "Waquf" (pause) and "Imāla" (tilting of vowel sounds) Mr. Saad Mohammed Al-Zahrani 5. The impact of contextual relations on the semantic transformation of the verb Dr. Mouhamed Diakho